A influência da colonialidade no currículo de uma escola de ensino fundamental de Cachoeiro de Itapemirim/ES - Tesch, Euza Alves de Souza (2024)
This research aims to analyze the relationship between coloniality and the curriculum in a primary school in Cachoeiro de Itapemirim/ES, seeking to map the resistance movements to this form of epistemological domination. The specific objectives were: a) to analyze the school’s Political Pedagogical Project with the aim of identifying the curricular conceptions embedded in the document; b) to investigate teachers’ understanding of the curriculum and coloniality; c) to discuss pedagogical practices that include Afro-Brazilian knowledge; and d) to analyze the curricular movements/practices that take place in the daily life of a municipal school. Therefore, the dissertation discusses how coloniality is present in the school’s daily life, through the lack of a decolonial curriculum that addresses historical issues related to the struggles of Black people and other groups to claim their place in society. To support the analysis of the theme of this research, we drew on authors such as Ferraço (2011), Gallo (2013), Silva (2022), Quijano (2007; 2010), Walsh (2007, 2009, 2015), Mignolo (2005), and others. The choice of these theorists allows us to deepen our understanding of coloniality, encompassing its influence on Education, specifically in the school curriculum. In this research, we observed that discussions about Afro-Brazilian and Indigenous cultures are rare in schools, despite being an extremely relevant subject that impacts several aspects of students’ lives. To support this work, we adopted a qualitative research approach, specifically the cartographic intervention-research methodology. Thus, the analysis took place throughout the research, during data production, and in dialogue with theoretical interlocutors. The subjects involved in the research were 21 students from the 2nd-year morning class and 13 school teachers, including the school administrator and the pedagogues. For data production, we used tools such as observation, field notes, conversation networks, and document analysis. The analysis of the school’s Political Pedagogical Project indicated that this document needs to be revised for its functionality to be effective. However, we also observed the absence of curricular planning aimed at building decolonial practices, as well as some resistance movements that occur individually by teachers and students. The conversation networks revealed a diverse understanding of what the curriculum is, but there is a consensus among teachers that the curriculum must respect students’ realities and that there is always something that needs to be expanded. When analyzing the data produced in the conversation networks, we identified specific clues pointing to the intention of implementing a decolonial curriculum in the school. We also observed a desire among the teachers to implement a decolonial approach in the school, on the condition that it stems from collective planning and is developed at the beginning of the year. Moreover, during the research process, we mapped teaching movements opposing the imposition of the BNCC (Common National Curricular Base). The study, therefore, highlights the lack of implementation of Laws No. 10.639/03 and No. 11.645/08 in the participating public school, in the construction of new practices against a “whitened” curriculum. Thus, we observed the presence of racism in the school’s daily life, but some resistance movements are taking place, albeit sporadically. Finally, we verified the need for initial and continuing teacher education within an educational policy aimed at a decolonial curriculum